1972
DOI: 10.1021/jo00975a040
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modifications of zearalenone. I

Abstract: Chemical transformations of the aliphatic portion of the mold metabolite zearalenone were examined. Reactions at the C'-6 ketone and the C'-l double bond and positions adjacent to these reaction centers are reported.The reactions proved to be quite regioselective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…To confirm the putative structure of P16 as ZEN-11,12-oxide, ZEN was subjected to chemical epoxidation using m -chloroperbenzoic acid (mCPBA). As noted previously by Jensen et al , the olefinic double bond of ZEN is quite resistant to epoxidation. However, the profile obtained by LC-DAD-MS analysis of the reaction mixture after 5 h showed that, in addition to ∼55% unreacted ZEN, two peaks had formed that had [M − H] − ions at m / z 333, indicative of monooxygenated ZENs.…”
Section: Resultssupporting
confidence: 63%
“…To confirm the putative structure of P16 as ZEN-11,12-oxide, ZEN was subjected to chemical epoxidation using m -chloroperbenzoic acid (mCPBA). As noted previously by Jensen et al , the olefinic double bond of ZEN is quite resistant to epoxidation. However, the profile obtained by LC-DAD-MS analysis of the reaction mixture after 5 h showed that, in addition to ∼55% unreacted ZEN, two peaks had formed that had [M − H] − ions at m / z 333, indicative of monooxygenated ZENs.…”
Section: Resultssupporting
confidence: 63%
“…These compounds act on the human estrogen receptor in competition with 17-estradiol . In our own studies, zearalenone ( 15 ), both stereoisomers of zearalenol ( 16 , 17 ), and semisynthetic derivatives from hydrogenation, methylation, and acetylation were studied in comparison with the metabolites of P 0297. Zearalenone ( 15 ) and α-zearalenol ( 16 ) and their derivatives did not exhibit any activity against HSV1, while β-zearalenol ( 17 ) was the most potent among all compounds examined in this study (Table ). Hydrogenation of β-zearalenol ( 17 ) to β-zearalanol ( 21 ) resulted in decreased activities, while the methylation and acetylation products of 17 were inactive.…”
Section: Resultsmentioning
confidence: 99%
“…Pochonin C (6): brownish oil; HPLC, tR 6.6 min (system 1); 1 H NMR ([D6]DMSO, 500 MHz), see Table 2; 13 + , 349 (43), 347 (100) (system 5); EIMS m/z 402 (7), 400 (11) [M + H] + , 366 (6), 364 (6), 314 (3), 312 (7), 229 (12), 203 89), 201 (26), 186 (33), 184 (100), 157 (16), 155 (16), 121 (25), 96 (32); HREIMS m/z 400.0472 (calcd for C 18H18Cl2O6, 400.0480).…”
Section: Methodsmentioning
confidence: 99%
“…Returning to the chemical objectives of the New Lead Discovery Department, it had become evident by the mid 1970s that the random synthesis of compounds for screening was not a cost-effective way of making new discoveries. In its place, we decided to organize an enzyme inhibitor design project and enlisted two expert consult- (12) interest in our laboratories. It reduces histamine levels most rapidly in tissues in which there is a high turnover of histamine and it is active, especially when chronically administered, in various animal models of allergic inflammation, ulcers, and asthma.…”
Section: E B Hershberg Award Addressmentioning
confidence: 99%